(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the types of meanings and meaning relationships contained in the novel A Business of Forgetting by Boy Candra. Semantic studies in literary works are important to understand the message, value, and meaning conveyed by the author through the use of language. This study uses a qualitative descriptive method. The source of research data is in the form of the novel A Business Forgets by Boy Candra, while the research data is in the form of words, phrases, sentences, and dialogues that contain elements of meaning and meaning relationships. Data is collected through reading and recording techniques, then analyzed using content analysis techniques with the stages of identification, classification, interpretation, and drawing conclusions. The results of the study show that the novel contains various types of meanings, namely lexical, grammatical, denotative, connotative, and associative meanings. In addition, various meaning relationships were found which included synonyms, antonyms, hyponymi, meronymiy, polysemis, and homonymies. Connotative and associative meanings seem to be predominantly used to strengthen the expression of characters’ emotions and build a narrative atmosphere, while synonym, antonymy, and polysemitic relationships play a role in enriching language variations and deepening the meaning conveyed by the author. This research is limited to semantic analysis in one literary work so that the results cannot be generalized to other works.